UNDERSTANDING PANCASILA IN THE MAQASHID-BASED FRAMEWORK AND ITS RELEVANCE TO INDONESIAN RELIGIOUS HARMONY: A DIALOGUE APPROACH - Syahbudi Syahbudi (istinbath, 2021)
Studies on maqashid al-sharia or the aims of Islamic law often seek to understand the philosophical meaning of public interest (maslahah), such as objective to preserve faith, life, reason, offspring, and wealth. This article develops the idea of the maqashid-based frame work for contextualization of Pancasila, especially in religious life. This article used the dialogue approach by Martin Buber (w. 1965), which are the theory of I-It, I-Thou, and I of The I-it and the idea of totality initiated by Emanuel Lévinas (w. 1995). The purpose of this article provides a new way of interpreting to the three pillars of maslahah; enhancements (tahsiniyat), desirable (hajiyat), and essential (daruriyat). I argue that mutual respect is the central idea of the dialogue approach in the realization of maslahah. Furthermore, the nexus that needs to be developed between maslahah and Pancasila is intersubjective model. On this basis, the mutual respect is relevant to reinforce and be integrated with Pancasila values for strengthening the religious harmony in Indonesia.